The theory of social representations in environmental studies - Fagundes, Beatriz (UFPR, 2009)
This article has for finality to present a reflection about the Theory of Social Representations, created by Moscovici in 1961, up from its historical context after looking for to understand like ordinary people build social representations about certain phenomenon and how they contribute to the geographic studies.